2006
DOI: 10.2466/pr0.99.3.794-798
|View full text |Cite
|
Sign up to set email alerts
|

Order of Question Presentation and Correlation between Judgments of Comparative and Own Risk

Abstract: Unrealistic optimism is often assessed using a single question asking for an estimate of comparative risk. However, it has been proposed that individuals treat such a question essentially as though it were only about their own risk. This proposal leads to the prediction that, when the questions about own risk and comparative risk are asked in sequence, the correlation between the resulting estimates should be lower if the question about own risk comes first than if the question about comparative risk comes fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Darker et al (2007) also found no question order effects in belief elicitation to open-ended questions used in a theory of planned behavior study of walking as exercise. Gold and Barclay (2006) found significant differences due to question order in correlations between judgments of one' s own risk and of an adverse event occurring (e.g., "What is the chance that you will get into a car accident in the next year?") and judgments of the risk of others (e.g., "What is the chance the average person will get into a car accident in the next year?").…”
Section: Health and Safety Studiesmentioning
confidence: 99%
“…Darker et al (2007) also found no question order effects in belief elicitation to open-ended questions used in a theory of planned behavior study of walking as exercise. Gold and Barclay (2006) found significant differences due to question order in correlations between judgments of one' s own risk and of an adverse event occurring (e.g., "What is the chance that you will get into a car accident in the next year?") and judgments of the risk of others (e.g., "What is the chance the average person will get into a car accident in the next year?").…”
Section: Health and Safety Studiesmentioning
confidence: 99%
“…Darker, French, Longdon, Morris, and Eves (2007) also found no question order effects in belief elicitation to open-ended questions used in a theory of planned behavior study of walking as exercise. Gold and Barclay (2006) found significant differences resulting from question order in correlations between judgments of one's own risk and of an adverse event occurring (e.g., "What is the chance that you will get into a car accident in the next year?") and judgments of the risk of others (e.g., "What is the chance the average person will get into a car accident in the next year?").…”
Section: Health Studiesmentioning
confidence: 99%